Gd-EOB-DTPA-enhanced MRI T1 relaxometry as an imaging-based liver function test compared with 13C-methacetin breath test. (March 2020) - Theilig, Dorothea; Tsereteli, Ana; Elkilany, Aboelyazid; Raabe, Philip; Lüdemann, Lutz; Malinowski, Maciej; Stockmann, Martin; Pratschke, Johann; Hamm, Bernd; Denecke, Timm; Geisel, Dominik
Background: Gadolinium ethoxybenzyl diethylenetriaminepentaacetic acid (Gd-EOB-DTPA)-enhanced magnetic resonance imaging (MRI) can be used as an imaging-based liver function test. This study aims to further corroborate its validity. Purpose: To compare Gd-EOB-DTPA-enhanced MRI as an imaging-based liver function test with the 13 C-methacetin breath test. Material and Methods: Fifty-three patients who underwent Gd-EOB-DTPA-enhanced MRI T1 relaxometry before and 20 min after intravenous Gd-EOB-DTPA administration as well as a 13 C-methacetin breath test (LiMAx test) were retrospectively analyzed. T1 relaxation times of liver parenchyma, total liver volume (TLV), and functional liver volume (FLV) were determined. Pearson correlations, multiple linear regression analysis, and receiver operating characteristic curve analysis were performed with indices derived from T1 relaxometry, liver volumetry, and laboratory parameters to identify the best predictor of liver function as determined by the LiMAx test. Results: T1 reduction rate (T1 RR), T1 RR × TLV, T1 RR × FLV, and T1 relaxation time 20 min after intravenous Gd-EOB administration showed a statistically significant correlation with LiMAx and discriminatory capacity between patients with LiMAx of > and < 315 µg/kg/h. Of the indices investigated, T1 RR showed the best discriminatory capacity and proved to be the only statistically significant parameter in multiple linear regression analysis. Conclusion: Gd-EOB-DTPA-enhanced MRI as an imaging-based liver function test also correlates with the LiMAx test which in turn reflects cytochrome P450 function. The T1 reduction rate of the liver on Gd-EOB-DTPA-enhanced MRI allows prediction of liver function as determined by the LiMAx test both for 1.5 and 3.0 T.